PACE UNIVERSITY, BLENDED LEARNING AND LOCALNESS: A MODEL THAT WORKS - Sachs, David (Online Learning, 2007)
Several forms of blended learning at Pace University offer flexible options for learners, and its growth reflects its appeal to traditional and corporate learners.